Special edition using Microsoft Expression Web - Cheshire, Jim (Que, 2006)
Special Edition Using Microsoft Expression Web We crafted this book to grow with you, providing the reference material you need as you move toward Expression Web proficiency and use of more advanced features. If you buy only one book on Expression Web, Special Edition Using Microsoft Expression Web is the only book you need. Create standards-compliant websites with Expression Web that will work consistently in all browsers. Become proficient in the use of CSS by learning how to use the powerful CSS tools in Expression Web. Learn how to take advantage of ASP.NET without the need to write any code. Learn how to use Expression Web with the free Visual Web Developer Express Edition to develop robust ASP.NET applications. Add dynamic, interactive content with Behaviors and Layers. Design your website for accessibility using both Section 508 and WCAG compliance. Category Web Development Covers Microsoft Expression Web User Level Intermediate-Advanced "There's definitely more to this book than just how to use Expression Web. The chapter on tag properties not only clearly explains Expression Web's Tag Properties task pane, but it also alleviates some of the mystery behind the use of tags in HTML. This is a great book for all users of Expression Web!"--Detra Newhouse, Readiness Lead, Microsoft Corporation Jim Cheshire is the owner of Jimco Software, the most well-known source of freeware add-ins for Microsoft FrontPage, and is the author of Special Edition Using Microsoft Office FrontPage 2003. Jim has been featured in numerous publications including MSDN Magazine and PC Magazine. Jim previously worked on the FrontPage team at Microsoft and is currently an Escalation Engineer on the ASP.NET and IIS teams. On the CD-ROM Sample files from the author FREE! full version of Logo Creator (retail value of $39.95) FREE! full version of DHTML Menu Builder Lite (retail value of $25) Electronic version of this book in Adobe's Portable Document Format (PDF) Introduction xxix Part I An Overview Chapter 1 A Tour of Expression Web 3 Part II Web Sites in Expression Web Chapter 2 Creating a Web Site 25 Chapter 3 Importing a Web Site 41 Chapter 4 Web Site Management and Reporting 67 Chapter 5 Publishing a Web Site 83 Chapter 6 Using Personal Web Packages 93 Part III Creating and Editing Web Content Chapter 7 Creating Pages and Content 103 Chapter 8 Using Web Page Views 127 Chapter 9 Using Tab ...